2021
DOI: 10.1088/1755-1315/677/3/032019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between milk yield and the service period duration of cows

Abstract: In the Sverdlovsk Region, the breeding stock of the black-and-white Ural breed was covered with the seed of servicing bulls of Canadian, Danish and German selection. They are able to show good average daily milk yields throughout lactation, to produce for a long time without a sharp decrease in milk yield, but at the same time, the problem of a decrease in the reproductive ability of cows and, as a consequence, a decrease in the productive longevity of the breeding stock was identified. The purpose of the work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
1
0
2
Order By: Relevance
“…In this study, there may be different reasons for the higher milk yield and longer lactation period in 3-year-old buffaloes. These reasons may be due to individual differences that cause variation within the herd including body weight, body condition score, gestation period and udder diseases or may be related to farm management (Akçapınar and Özbeyaz, 2021;Qureshi et al, 2007;Khan et al, 2008;Gorelik et al, 2021). In this study, it was also observed that the lactation length and milk yield were higher in buffaloes with a long service period (>300 days).…”
Section: Discussionsupporting
confidence: 53%
“…In this study, there may be different reasons for the higher milk yield and longer lactation period in 3-year-old buffaloes. These reasons may be due to individual differences that cause variation within the herd including body weight, body condition score, gestation period and udder diseases or may be related to farm management (Akçapınar and Özbeyaz, 2021;Qureshi et al, 2007;Khan et al, 2008;Gorelik et al, 2021). In this study, it was also observed that the lactation length and milk yield were higher in buffaloes with a long service period (>300 days).…”
Section: Discussionsupporting
confidence: 53%
“…Milk yield was studied during 305 days of lactation, with the determination of fat and protein in milk (Abugaliyev et al, 2019;Alekseeva and Chetvertakov, 2021;Bolotova and Chalova, 2020;Grinchuk and Nesterov, 2021;Gorelik et al, 2021b).…”
Section: Methodsmentioning
confidence: 99%
“…Одним из более эффективных методов совершенствования породы является разведение по линиям. Эта важная форма включает в себя такие методы, как отбор, подбор, родственное и неродственное спаривание, работу с линия ми и семействами [15,16].…”
Section: зоотехния и ветеринарияunclassified